Pelatihan Goal Setting terhadap Motivasi Kerja Karyawan di PT.X Sragen - Endah Mutiara Sari; Wiwien Dinar Pratisti; Susatyo Yuwono (Universitas Islam Indonesia, 2021)
Work motivation that becomes a drive for someone in completing their work is important to be maintained and improved. The purpose of this research was to determine the effectiveness of goal setting training to improve work motivation for employees. This study uses a pretest-posttest control group design. Subjects of this research were 24 employees of PT X Sragen, which is divided into experimental and control groups. Measurement of work motivation was using The Multidimensional Work Motivation Scale. The data results were analyzed by ANOVA mixed design analysis. The results of the interaction test work motivation scores between the experimental and control groups crossed with the score measurement time (pretest-posttest-follow up) showed an F-count value of 27,604 and a significance of 0,000 and partial eta squared 0,556 that means goal setting training is effective to increase work motivation on employees. Thus, employee can empower their clearer and more targeted goals to be more motivated at work..